Study on the synergistic effect of calcium and aluminum on improving ash fusion temperature of semi-coke. Issue 3 (4th March 2022) - Lin, Rongying; Lin, Chenhao; Li, Yuanyuan; Lin, Bo
ABSTRACT: In order to make better use of the low ash fusion temperature semi-coke, increasing the coal's ash fusion temperature is the key to improving the coal gasification process. In this paper, through comparing with the effect of alumina and calcium oxide alone on ash fusion temperature of semi-coke, the synergistic effect of alumina and calcium oxide on the coal ash was studied. The effects of refractory agent A (rich in alumina) and B (rich in both alumina and calcium oxide) on the ash fusion temperature were also studied. The minerals evolutions during the ash melting process before and after A, B refractory agents were added were studied by X-ray diffractometer (XRD) and ternary phase diagram of FactSage. The results showed that adding a high amount of Al2 O3 and a small amount of CaO to ash had a synergistic effect on increasing the ash fusion temperature. The formation of both mullite and anorthite had the synergy effect on increasing the ash fusion temperature. This was consistent with FactSage results.